ANALISA KEPADATAN TANAH PADA JALAN LINGKAR SELATAN RUAS JALAN CISAAT SUKABUMI - Januri Ismayana; Bambang Jatmika; Rico Sihotang (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2019)
The term "land" in the mechanical field of land is intended to cover all materials from clay to gluttony; so all natural deposits are related to civil engineering except stone. Stone becomes its own science, namely stone mechanics. Soil pavement is placed on the surface of the land, thus the overall quality and durability of pavement construction cannot be separated from the nature of the subgrade. A good subgrade for road construction is subgrade originating from the location itself or nearby, which has been compacted to a certain density level so that it has good carrying capacity and the ability to maintain volume changes during the service period even though there are differences in environmental conditions and local soil types. The nature of each type of soil depends on texture, density, moisture content, environmental conditions, and so on. In order to make it easier to study and discuss the properties of the soil that will be used as soil base material, the soil is grouped based on the nature of plasticity and grain size. The carrying capacity of the subgrade can be estimated by using the classification results or from CBR checks, loading test plates and so on.